2020
DOI: 10.1186/s12877-020-01769-4
|View full text |Cite
|
Sign up to set email alerts
|

Can in-hospital or post discharge caregiver involvement increase functional performance of older patients? A systematic review

Abstract: Background Regaining pre-hospitalization activity levels is only achieved in 30–50% of older patients. Extra physiotherapy time has been proven to improve functional outcome and shorten length of stay, but is costly. Considering their key role in caring for older people, involving informal caregivers in rehabilitation might further improve functional performance. Aim To determine if in-hospital or post discharge caregiver involvement can increase functional performance in older adults. The secondary aim was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…13 Healthcare environments can impact staff efficiency, well-being Open access and retention, 1 with flow-on effects for patient care. Family and caregiver involvement can improve patient outcomes, 57 yet caregivers often feel ignored or alienated in inpatient stroke rehabilitation environments. 58 Future research should consider the impact of the built environment on staff and family/caregivers and how the environmental needs and priorities of these groups can be balanced with patients' needs.…”
Section: Discussionmentioning
confidence: 99%
“…13 Healthcare environments can impact staff efficiency, well-being Open access and retention, 1 with flow-on effects for patient care. Family and caregiver involvement can improve patient outcomes, 57 yet caregivers often feel ignored or alienated in inpatient stroke rehabilitation environments. 58 Future research should consider the impact of the built environment on staff and family/caregivers and how the environmental needs and priorities of these groups can be balanced with patients' needs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the program led to greater satisfaction among relatives regarding the provided care [ 27 , 28 ]. Also, if cognitive dysfunction is recognised, relatives can be more intensively involved in the medical treatment during the admission, which can improve hospital outcomes [ 34 ]. Involving relatives in the care process may even reduce the number of readmissions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that family involvement has the potential to optimize patient outcomes, such as illness and recovery experience, as well as redirecting family psychological distress into an active participatory role, and supporting HCPs with the constraints of time and staffing [ 95 – 97 ]. Moreover, caregiver involvement may lead to better functional performance after discharge [ 98 ]. However, due to limited research on family participation in inpatient mobilization, the evidence on the effects of interventions that include family participation is low, and it is therefore difficult to draw strong conclusions.…”
Section: Discussionmentioning
confidence: 99%